Prostatic carcinoma in a dog - Faridah Noor,; Abdul Rahman, Sheikh Omar; Saad, Mohamad Zamri (Persatuan Doktor Veterinar Malaysia, 1984)
A case of prostatic carcinoma was observed in a 10 year-old Doberman Pinscher with a history of urinary incontinence of one month duration. The tumour had metastases in the serosa of the urinary bladder, omentum and mesentery filling the pelvic cavity.